Enterovirus genotype diversity with emergence of coxsackievirus A2 circulating in pediatric patients with acute gastroenteritis in Thailand, 2019–2022 - Xie, Zhenfeng; Khamrin, Pattara; Jampanil, Nutthawadee; Yodmeeklin, Arpaporn; Ukarapol, Nuthapong; Maneekarn, Niwat; Kumthip, Kattareeya (Frontiers in Microbiology, 2024)
Enteroviruses (EVs) are recognized as potential causative agents of acute gastroenteritis (AGE) in children worldwide. This study aimed to investigate the epidemiology and molecular characteristics of EV infection in children admitted to hospitals with AGE in Chiang Mai, Thailand from 2019 to 2022. Methods: A total of 1148 fecal samples collected from patients with AGE were screened for the presence of EV using RT-PCR. The prevalence, co-infection with common diarrheal viruses, and seasonal pattern of EV were examined. The genotypes of EV were identified based on the VP1 sequence and phylogenetic analysis. Results: The overall prevalence of EV in AGE patients was 8.8% (101/1148).After the COVID-19 outbreak in 2019, a significant decrease in the EV infection rate and genotype diversity was observed (p<0.05). EV infection alone was observed in 68.3% (69/101) of cases while coinfection with other enteric viruses was 31.7% (32/101). The seasonal pattern of EV infection showed a peak prevalence during the rainy season. EV species A was the most prevalent(37.5%), followed by species B (32.3%), species C (29.2%), and species D (1.0%). Twenty-five genotypes of EV were identified with the most predominant of the coxsackievirus being A2 (CV-A2) (13.5%), CV-B2 (7.3%) and CV-A24(5.2%). Conclusions: Our data demonstrate a significant decrease in the prevalence and diversity of EV circulating in AGE patients during the COVID-19 pandemic and highlight the emergence of CV-A2 during this study period. These findings contribute to a better understanding of the molecular epidemiology and diversity of EV in patients with AGE and provide useful information for further investigation into the potential association between specific EV genotypes and AGE in future studies.